Five Nights at Freddy's: The Fourth Closet - Book 3 - Cawthon, Scott, 1971-; Breed-Wrisley, Kira. (New York : Scholastic, Inc., 2018)
"What really happened to Charlie? Its the question that John cant seem to shake, along with the nightmares of Charlies seeming death and miraculous reappearance. John just wants to forget the whole terrifying saga of Freddy Fazbears Pizza, but the past isnt so easily buried.Meanwhile, theres a new animatronic pizzeria opening in Hurricane, along with a new rash of kidnappings that feel all too familiar. Bound together by their childhood loss, John reluctantly teams up with Jessica, Marla, and Carlton to solve the case and find the missing children. Along the way, theyll unravel the twisted mystery of what really happened to Charlie, and the haunting legacy of her fathers creations."--Page 4 of cover.
Accelerated Reader
Keywords: Five Nights at Freddys (Video game) -- Juvenile fiction; Robots -- Juvenile fiction; Pizzerias -- Juvenile fiction; Survival -- Juvenile fiction; Zombies -- Juvenile fiction; Horror tales -- Juvenile fiction; Kidnapping -- Fiction; Pizzerias -- Fiction; Horror stories; Horror fiction